Fly-FUCCI: a versatile tool for studying cell proliferation in complex tissues - Zielke, Norman; Korzelius, Jerome; Straaten, Monique van; Bender, Katharina; Schuhknecht, Gregor F. P.; Dutta, Devanjali; Xiang, Jinyi; Edgar, Bruce (Cell reports, 2014)
One promising approach for in vivo studies of cell proliferation is the FUCCI system (fluorescent ubiquitination-based cell cycle indicator). Here, we report the development of a Drosophila-specific FUCCI system (Fly-FUCCI) that allows one to distinguish G1, S, and G2 phases of interphase. Fly-FUCCI relies on fluorochrome-tagged degrons from the Cyclin B and E2F1 proteins, which are degraded by the ubiquitin E3-ligases APC/C and CRL4Cdt2, during mitosis or the onset of S phase, respectively. These probes can track cell-cycle patterns in cultured Drosophila cells, eye and wing imaginal discs, salivary glands, the adult midgut, and probably other tissues. To support a broad range of experimental applications, we have generated a toolkit of transgenic Drosophila lines that express the Fly-FUCCI probes under control of the UASt, UASp, QUAS, and ubiquitin promoters. The Fly-FUCCI system should be a valuable tool for visualizing cell-cycle activity during development, tissue homeostasis, and neoplastic growth.
Gesehen am 26.08.2020